Teaching Writing Skills Using Invitation Cards Through a Creative Learning Models for Junior High School Students - Mulkiah, Sinta; Inayah, Ratih (PROJECT (Professional Journal of English Education), 2025)
Writing skills are very valuable in various contexts, one of which is the world of creativity. By having good and correct writing skills, people can more effectively convey their ideas through writing. This research also aims to determine students responses to the implementation of writing skills training activities using invitation cards, where the invitation cards are used as a tool in teaching writing skills to class VIII students at SMP PGRI 5 Cimahi within the framework of a creative learning model. In this research students can develop their ideas and creativity in this teaching learning. The method in this research used descriptive qualitative research using direct research in the field by researcher. This data collection source was taken directly when the researcher carried out of GISMA (Gerakan IKIP Siliwangi Mengajar). The data analysis in this study, the researcher stated that in this study students work was assessed in several aspects. Based on the results of the data can be concluded as successful and able to complete the research effectively, and the researcher explain how dramatically students’ writing skills are improved when the invitation card writing exam, which is based on the creative learning paradigm is implemented.